An unexpected diagnosis of a 57-year-old women with migratory pulmonary infiltrates - Elad Mor; Alexandra Balbir-Gurman; Ludmila Guralnik; Inna Naroditski; Morad Zayoud; Yaniv Dotan (Respiratory Medicine Case Reports, 2023)
A 57-year-old female presented with sudden shortness of breath and migratory pulmonary infiltrates on imaging, which corresponds with a diagnosis of cryptogenic organizing pneumonia. Initial treatment with corticosteroids showed only mild improvement during follow-up. BAL was performed and revealed diffuse alveolar hemorrhage. Immune testing showed positive P-ANCA with positive MPO, leading to a diagnosis of microscopic polyangiitis.